Influence of Rootstocks on Growth Yield and Fruit Composition of Thompson Seedless Grapes Grown in the Pune Region of India - Satisha, J.; Somkuwar, R.G.; Sharma, J.; Upadhyay, A.K.; Adsule, P.G. (South African Journal of Enology and Viticulture, 2016)
The use of rootstocks is gaining importance in Indian viticulture due to problems associated with abiotic stresses, such as drought and salinity, and also to improve scion characteristics. Thompson Seedless is the only commercial cultivar grown for both fresh consumption and raisin making. Dog Ridge was the only popular rootstock used by grape growers prior to late 1990s. But this rootstock was known to induce more vigour in scions, resulting in reduced bud fruitfulness and thereby fruit yield. To identify alternate rootstocks suitable for Thompson Seedless, a study was initiated in the National Research Centre for Grapes, Pune, India during the year 2001. Five rootstocks with own rooted vines were evaluated in this study. During the initial years, Thompson Seedless grafted on Dog Ridge produced the highest yield, with good quality fruit. Over the years we could observe uneven bud sprouting, gaps on the cordon due to dead wood formation, and reduced yield in vines grafted on Dog Ridge rootstocks. In contrast, Thompson Seedless grafted on 110R performed well in terms of moderate vigour, increased fruitfulness and consistently higher yield. Dog Ridge and St. George produced a lower yield, owing to increased vigour measured in terms of pruning weight, total shoot length and cane diameter. Rootstocks 110R, 1103P and 99R are also known to increase water-use efficiency during critical growth stages of fruit bud differentiation and full bloom. No significant influence of rootstocks was observed for most of the fruit composition parameters. Larger and bolder berries were produced on Dog ridge and 110R rootstock, while they were the smallest on own rooted vines.